2014
DOI: 10.1186/1471-2229-14-146
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of genetic variation in rootstocks and scions of old olive trees – a window into the history of olive cultivation practices and past genetic variation

Abstract: BackgroundPast clonal propagation of olive trees is intimately linked to grafting. However, evidence on grafting in ancient trees is scarce, and not much is known about the source of plant material used for rootstocks. Here, the Simple Sequence Repeat (SSR) marker technique was used to study genetic diversity of rootstocks and scions in ancient olive trees from the Levant and its implications for past cultivation of olives. Leaf samples were collected from tree canopies (scions) and shoots growing from the tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 29 publications
9
69
0
1
Order By: Relevance
“…Analysis of multi-locus genotypes (MLGs) and grouping of MLGs into multi-locus lineages (MLLs) reduced the probability of mistakes resulting from SSR genotyping errors, thus permitting the comparison of naturally growing populations with grafted old olive trees [30]. The multi-locus lineage analysis (Table 2) showed that 10 trees each of the naturally growing and cultivated trees at BGR belonged to the most commonly cultivated regional clone MLL1 [33]. One of the remaining nine trees belonged to MLL7 and the remaining eight trees were assigned to site-specific single occurrence MLLs of which seven were found in naturally growing trees.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of multi-locus genotypes (MLGs) and grouping of MLGs into multi-locus lineages (MLLs) reduced the probability of mistakes resulting from SSR genotyping errors, thus permitting the comparison of naturally growing populations with grafted old olive trees [30]. The multi-locus lineage analysis (Table 2) showed that 10 trees each of the naturally growing and cultivated trees at BGR belonged to the most commonly cultivated regional clone MLL1 [33]. One of the remaining nine trees belonged to MLL7 and the remaining eight trees were assigned to site-specific single occurrence MLLs of which seven were found in naturally growing trees.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, MLLs of suckers and scions of cultivated old olive trees are indicated. Site-specific and single occurrence (SO) MLLs are indicated in bold; MLL1 and 7 represent the most common MLLs found in scions and suckers of old cultivated trees, respectively [33]. MLLs in the BGR population represent the supposedly cultivated (C) and naturally growing (wild) trees…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancient trees have been recently investigated using SSR markers (Lazović et al 2016;Sakar et al 2016b;Barazani et al 2014;Petruccelli et al 2014;Salimonti et al 2013). Chalak et al (2015) analysed 73 olive trees, including six monumentals from four main Lebanese areas, with 12 nuclear SSRs and 39 plastid DNA markers.…”
Section: Ssrsmentioning
confidence: 99%
“…(Brun 1986). Cette technique fort ancienne existe à l'état de trace désormais en Espagne et au Levant et elle a attiré l'attention récemment des généticiens (Diez et al 2011, Barazani et al 2014. Ces derniers suggèrent que cette méthode a pu être une des anciennes techniques de domestication de l'olivier et serait passée quelque peu inaperçue.…”
Section: Résultatsunclassified